21st Century Astronomy - Hester Jeff (Norton, 2006)
The Second Edition of 21st Century Astronomy reaffirms its status as the most current and authoritative text for introductory courses. Written by a team of specialists who are also experienced teachers, this accessible text fosters scientific literacy by relating core concepts in modern astronomy to the real-world process of science. Retaining the lively prose and narrative style of the previous edition, the text now offers improved pedagogy, an expanded art program, and dynamic new multimedia tools for students and instructors. The text is also now available in a comprehensive one-volume edition, a flexible ebook format, or two separate volumes, one focusing on the solar system and the other focusing on stars and galaxies.